2019
DOI: 10.1038/s41598-019-45043-z
|View full text |Cite
|
Sign up to set email alerts
|

B-mode ultrasound for the assessment of hepatic fibrosis: a quantitative multiparametric analysis for a radiomics approach

Abstract: Hepatic fibrosis and cirrhosis are a growing global health problem with increasing mortality rates. Early diagnosis and staging of hepatic fibrosis represent a major challenge. Currently liver biopsy is the gold standard for fibrosis assessment; however, biopsy requires an invasive procedure and is prone to sampling error and reader variability. In the current study we investigate using quantitative analysis of computer-extracted features of B-mode ultrasound as a non-invasive tool to characterize hepatic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Approximately 1 million people die from complications of cirrhosis all over the world each year. In addition, cirrhosis accounts for 1.6% and 2.1% of the worldwide burden of disability-adjusted life years and years of life lost, respectively 1 , 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1 million people die from complications of cirrhosis all over the world each year. In addition, cirrhosis accounts for 1.6% and 2.1% of the worldwide burden of disability-adjusted life years and years of life lost, respectively 1 , 6 .…”
Section: Discussionmentioning
confidence: 99%
“…1.2% and a mortality rate of 0.4%. Other limitations of liver biopsy include inter- and intraobserver variability and sampling error 6 8 . Such limitations emphasize the need for developing an alternative noninvasive method for identifying the etiology of liver cirrhosis especially in patients with indeterminate findings based on standard noninvasive diagnostic algorithms including physical examination, laboratory testing, biochemical markers, and imaging modalities 5 , 6 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…As hepatic fibrosis developed, these later increases in echogenicity and coarseness could be related to an excessive accumulation of extracellular matrix components in the liver parenchyma [ 41 ]. Although increase in liver echogenicity is associated with steatosis as well as fibrosis [ 42 ], histological assessment of rat liver tissues in our previous study showed that DEN administration in rodents did not cause liver steatosis [ 5 ]. Hence, the accompanying changes in the liver texture features along with increased echogenicity of liver tissue induced by DEN ingestion are more likely due to fibrotic changes rather than steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate assessment of liver status is essential for the prognosis, monitoring and management of CHB patients. D Souza et al studied the B-mode ultrasound features of the liver in a rat model to assess liver fibrosis (32). The computer algorithm extracted quantitative parameters representing brightness (echo intensity and liver and kidney index) and variance (heterogeneity) to study the anisotropy of the liver.…”
Section: Screening Diagnosis Classification and Stagingmentioning
confidence: 99%